2006
DOI: 10.1162/qjec.121.3.999
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Intergenerational Associations: Lessons from Swedish Adoption Data*

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
331
5
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(368 citation statements)
references
References 18 publications
31
331
5
1
Order By: Relevance
“…M1 in Table 5 shows the earnings association between G2 and G3. The coefficient is statistically significant and 0.22, which in line with similar two-generation estimates in other studies for Sweden, typically ranging between 0.2 and 0.3 (Björklund and Jäntti 1997;Björklund, Lindahl and Plug 2006;Lindahl et al 2012). Adding PG1 earnings (M2) somewhat reduces the G2 coefficient, but shows no indication of a grandparental impact over and above the parental one.…”
Section: Earningssupporting
confidence: 86%
See 1 more Smart Citation
“…M1 in Table 5 shows the earnings association between G2 and G3. The coefficient is statistically significant and 0.22, which in line with similar two-generation estimates in other studies for Sweden, typically ranging between 0.2 and 0.3 (Björklund and Jäntti 1997;Björklund, Lindahl and Plug 2006;Lindahl et al 2012). Adding PG1 earnings (M2) somewhat reduces the G2 coefficient, but shows no indication of a grandparental impact over and above the parental one.…”
Section: Earningssupporting
confidence: 86%
“…Biological (genetic) factors are of course not dependent on residential proximity and interaction between generations. To the extent that genetics has an impact on ability and socioeconomic status (see, e.g., Beenstock 2012; Black and Devereux 2011;Björklund, Jäntti, and Solon 2007;Björklund, Lindahl, and Plug 2006) it is possible that it could explain some of the maternal grandfather influence, while the impact from paternal grandfathers should be lower because most of the effect is mediated by the inclusion of father characteristics (but perhaps not completely so, as we only measure father's socioeconomic status and not all traits need to be equally manifested in each generation). Thus, a stronger association in status, on average, between maternal grandfather and grandson than between paternal grandfather and grandson could be interpreted as support for this kind of biological pathway in cases when it is not contingent upon geographical proximity.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors exploit datasets in which either twins or adopted children are present to use a fixed effect approach. The presence in a dataset of individuals that share the same genetic traits but that live in different families (for example the children of twins, as in Behrman and Rosezweig, 2002, in Currie and Moretti, 2007, and in Pronzato, 2011 or that have a common family background, but did not receive the same genetic transmission (for example natural and adopted children as in Plug, 2004) or, finally, individuals for which information is available for both natural and adoptive parents (as in Bjorklund et al, 2006) allows to disaggregate the effects of genetic transmission form the effects of family environment.…”
Section: Background Literaturementioning
confidence: 99%
“…We also look separately to the effect of mothers and fathers since past researches have shown that each parent can affect differently her children's decisions and behaviour (Anger S. and Heineck G., 2010; Ermish an Francesconi, 2002; Louriero et al 2006;Bjorklund et al, 2006;Farré et al, 2009;Dohmen et al, 2011;and Mullan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also when adoption is used as a natural experiment to exclude genetically transferred ability as a factor of influence, a significant relationship with income remains (Plug & Vijverberg, 2005). This result is robust to controlling for characteristics of the biological parents and extending the focus to economic outcomes of the children (Björklund, Lindahl, & Plug, 2006). Hence, parental income appears to constitute an important determinant of success in school and the labor market.…”
Section: Introductionmentioning
confidence: 85%